Files for Fiction - Orlando, Eleonora Eva (2016)
In this essay, I appeal to the mental file approach in order to give an anti- realist semantic analysis of statements containing fictional names. I claim that fictive and parafictive uses of them express conceptual, though not general, propositions constituted by mental files, anchored in the conceptual world of the corresponding fictional story. Moreover, by positing a referential shift determined by the presence of a simulative referential intention characteristic of those uses, it is possible to take them to be true with respect to those conceptual worlds. As for metafictive uses, since they are grounded on mixed intentions, they are considered to express hybrid propositions, partly conceptual and partly referential.